Description of a new species of Namalycastis (Annelida: Nereididae: Namanereidinae) from the Brazilian coast with a phylogeny of the genus - Alves, Paulo Ricardo; Santos, Cinthya Simone Gomes (Zootaxa, 2016)
The subfamily Namanereidinae represents one of the few groups of Polychaeta strongly adapted to low salinity and freshwater. Recently, some new species of the subfamily have been described, but no new phylogenetic analyses for the group have been undertaken since 1999. Here, we describe a new species of Namanereidinae, Namalycastis caetensis sp. nov., and provide a morphology-based phylogenetic analysis of the genus Namalycastis with the aim of assessing the evolutionary relationships for this new species. The designation of this new species is supported by the presence of elongated falcigers (also known as pseudospinigers, an unusual character in the genus), lack of an anterior cleft in the prostomium, slightly indistinct cirrophores, four pairs of tentacular cirri, and subconical acicular ligulae. Our results suggest that Namalycastis caetensis is closely related to N. geayi and N. fauveli. The existence of poorly-characterized species, from a morphological and molecular point of view, still limits our understanding of Namanereidinae relationships.